The burden of aortic aneurysm in China from 1990 to 2019: findings from the Global Burden of Disease Study 2019 - Xinran Hou; Fan Zhang; Zhi Ye; Qian Xu; Lingjin Huang; Qulian Guo; Wei Liu; Lijun Wang; Maigeng Zhou; Peng Yin; Maoen Zhu (BMC Public Health, 2022)
Abstract Background Aortic aneurysm (AA) is a global public health concern. However, little is known about the disease burden of AA in China. Methods Following the general analytic strategy used in the Global Burden of Disease Study (GBD) 2019, we analyzed the mortality and years of life lost (YLLs) due to AA, stratified by sex, age, and province-level region in China from 1990 to 2019. The temporal trend of AA burden in China was analyzed and the main attributable risk factors for AA in China were also explored. Results In China, the total AA deaths were 17,038 (95% UI: 14,392-19,980) in 2019, an increase of 136.1% compared with that in 1990, with an age-standardized death rate (ASDR) of 0.93 (95% UI: 0.79-1.08) per 100,000 person-years in 2019, a decrease of 6.8%. Meanwhile AA caused 378,578 (95% UI: 315,980-450,479) YLLs in 2019, an increase of 102.6% compared with that in 1990, with a crude YLL rate of 26.6 (95% UI: 22.2-31.7) per 100,000 person-years, an increase of 68.6%. The AA mortality and YLLs were higher in males than in females. AA caused most YLLs in the 65- to 75-year-old age group. The AA mortality and YLLs varied significantly among provinces in China, and the change in ASDR showed a negative correlation with the sociodemographic index of different provinces, namely, more decline of ASDR in developed provinces. High systolic blood pressure was shown to be the most significant attributable risk factor for AA burden in both males and females, and smoking was another major attributable risk factor, especially in males. Conclusions The disease burden of AA increased significantly from 1990 to 2019 in China, with higher mortality and YLLs in males, senior populations, and among residents of most western provinces in China. High systolic blood pressure and smoking were two major attributable risk factors for AA mortality in China.